Growth Responses and Metal Accumulation in an Ornamental Plant (Osmanthus fragrans var. thunbergii) Submitted to Different Cd Levels. (17th April 2011) - Wu, Fu-Zhong; Yang, Wan-Qin; Zhang, Jian; Zhou, Li-Qiang
Abstract : To characterize the effects of Cd supplies on the accumulation efficiency of Cd, Pb, Zn, and Cu in an ornamental plant (osmanthus, Osmanthus fragrans var. thunbergii ), a pot experiment using current-year osmanthus in field was carried out in western China. Biomass and its components showed a decreasing tendency as Cd supply increased, though insignificant differences were observed between treatments with a low and no Cd supply. Cd supplies increased the concentrations of Cd and Pb in plants, but the concentrations of Zn and Cu in plant showed a decreasing tendency with the increase of Cd supplies. Cd supplies also increased Cd accumulation for the plant, although the highest Cd accumulation was observed at a low Cd supply (T1). A higher Pb accumulation in the osmanthus was also detected in T1 than the other treatments. However, Zn and Cu accumulations decreased with the increase of Cd supplies. The examined osmanthus showed relative higher Cd and Pb transfer efficiencies in the presence of Cd supplies, but Cd supplies can limit the transfer of Zn and Cu. The results suggested that the examined osmanthus has potential for use in metal-contaminated environments due to phytoremediation application in the soil.